Cardiovascular risk factors are associated with lower posterior-medial network functional connectivity in older adults - Léa Chauveau; Julie Gonneaud; Géraldine Poisnel; Brigitte Landeau; Antoine Garnier-Crussard; Anne-Lise Pitel; Daniel Roquet; Edelweiss Touron; Sacha Haudry; Florence Mezenge; Anne Chocat; Denis Vivien; et al. (Alzheimer’s Research & Therapy)
Abstract Background Cortico-hippocampal functional networks, specifically the anterior-temporal (AT) and posterior-medial (PM) systems, are crucial for memory and highly vulnerable to aging and Alzheimer’s disease (AD). While modifiable cardiovascular risk factors may offer prevention opportunities to preserve brain aging, their effects on AT/PM functional connectivity remain unknown. This study aims to investigate these associations in older adults, considering major risk categories and exploring potential interactions with protective lifestyle habits and AD risk factors. Methods One hundred thirty-one community-dwelling cognitively unimpaired adults aged 65 + were selected from the Age-Well trial, a French monocentric population-based study conducted from 2016 to 2020. Resting-state fMRI and cardiovascular risk assessments were performed at baseline and 18-month follow-up. Functional connectivity within the AT and PM networks was derived from seed-based analyses using the perirhinal and parahippocampal cortices as individual seeds, respectively. Generalized additive and linear mixed models assessed the effects of cardiovascular risk factors on AT/PM functional connectivity, including interactions with protective lifestyle habits and AD risk factors. Results Baseline mean age was 69 (65–84) years, with 63.5% women. Higher abdominal fat (95% CI: -0.00118, -0.00005; F = 5.39; P =.02), higher LDL cholesterol (95% CI: -0.01642, -0.00345; F = 10.40; P =.001), longer smoking duration (95% CI: NA; F = 3.89; P =.03) and greater alcohol consumption (95% CI: -0.01134, -0.00045; F = 4.66; P =.02) were consistently associated with lower PM connectivity, collectively explaining 11.4% of the variance. However, only LDL cholesterol survived multiple comparisons, possibly reflecting a more direct involvement in cardiovascular mechanisms affecting functional connectivity. No association was found with AT connectivity. Exploratory analyses showed that these relationships were independent of cerebral Aβ-positivity or APOE-ε4 carrier status and were unaffected by physical activity and Mediterranean diet when considered separately. Discussion This study highlights converging associations between higher cardiovascular risk factors and lower functional connectivity in cognitively unimpaired older adults, specifically affecting the PM—but not AT—network, and independent of AD risk. Targeting these specific modifiable factors may prevent age-related network alterations to promote cognitive health in aging. Trial registration information The Age-Well trial was registered with ClinicalTrials.gov on November 25, 2016 (identifier: NCT02977819).